Des souvenirs ethnobotaniques d’un écologue et des réflexions qui s’ensuivent, suivi d’un billet d’humeur - Jean-Paul Lescure (Revue d'ethnoécologie)
In this text the author looks back on his work and on those he directed regarding the uses of plants and environments. On the basis of this experience, he clarifies his conception of ethnosciences. And finally, he uses a few articles on European ethnobotany as a pretext for taking offense at the total lack of visibility of ethnobotany work on the French metropolitan territory and invites researchers to reinvest this area of research.